FORENSIC EXAMINATION IN ADMINISTRATIVE PROCEEDINGS: LEGAL NATURE AND PROCEDURAL STATUS OF THE EXPERT - Legenkyi, Mykola (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose: to clarify the essence and legal nature of forensic examination in administrative proceedings, to analyze scholars’ views on its definition, and to study the procedural status of a forensic expert. Research methods: the logical-semantic method was applied to define the concepts of "forensic examination" and "special knowledge." The dialectical method of cognition was used to determine the legal nature of forensic examination and the procedural status of the expert. Through analysis and synthesis, the peculiarities of forensic examination in administrative proceedings were identified. Results: the article presents a comprehensive study of the institution of forensic examination in administrative proceedings in Ukraine, which ensures objectivity and completeness in the consideration of public-law disputes. Attention is given to the analysis of scientific approaches to defining the concept of "forensic examination," demonstrating the polysemy and multi-aspect nature of this phenomenon. It is substantiated that forensic examination is a distinct legal institution requiring a consistent approach to its legal regulation and practical application. Its procedural significance lies in the ability to obtain a scientifically grounded opinion that serves as a means of evidence in a case. Considerable attention is devoted to specialized knowledge, which is an essential component of forensic expert activity, as well as to the legal status of the expert as a subject endowed with rights and obligations. The grounds for disciplinary liability of the expert and the limits of their professional activity are generalized. The article also separately examines the requirements for experts established by current legislation and the conditions for admission to conduct examinations. The conclusion is substantiated that the effectiveness of using forensic examination as a method of establishing the truth depends on the level of the expert’s professionalism. Discussion: the effectiveness of using forensic examination as a means of establishing the truth in administrative proceedings directly depends on the level of professionalism of the expert, their adherence to procedural and ethical standards, as well as the proper use by the court of the results of the expert’s study.